2017
DOI: 10.1103/physrevlett.118.110504
|View full text |Cite
|
Sign up to set email alerts
|

Loop Optimization for Tensor Network Renormalization

Abstract: We introduce a tensor renormalization group scheme for coarse graining a two-dimensional tensor network that can be successfully applied to both classical and quantum systems on and off criticality. The key innovation in our scheme is to deform a 2D tensor network into small loops and then optimize the tensors on each loop. In this way, we remove short-range entanglement at each iteration step and significantly improve the accuracy and stability of the renormalization flow. We demonstrate our algorithm in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
165
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(172 citation statements)
references
References 61 publications
6
165
1
Order By: Relevance
“…We find that the KAFHM ground state is a gapped QSL with the Z 2 topological order [3,74] and has a long correlation length, ξ ∼ 10 unit cells. We justify the TRG flow of modular matrices at critical points and argue that our estimation of the correlation length is valid within a distance of 30 unit cells or more, consistent with previous studies [77,78]. Such a long correlation length (ξ ∼ 10 kagome unit cells) might explain the DMRG's failure in identifying Z 2 topological order and the gapless behaviors in recent numerical simulations [69][70][71][72]79].…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…We find that the KAFHM ground state is a gapped QSL with the Z 2 topological order [3,74] and has a long correlation length, ξ ∼ 10 unit cells. We justify the TRG flow of modular matrices at critical points and argue that our estimation of the correlation length is valid within a distance of 30 unit cells or more, consistent with previous studies [77,78]. Such a long correlation length (ξ ∼ 10 kagome unit cells) might explain the DMRG's failure in identifying Z 2 topological order and the gapless behaviors in recent numerical simulations [69][70][71][72]79].…”
Section: Introductionsupporting
confidence: 59%
“…By studying the quantum critical state where the TRG simulation has the worst truncation errors, Refs. [77,78] found that the TRG simulation can handle a very large system size with a length of over 30 unit cells, since highly accurate critical exponents were obtained from calculations on such large systems. In the previous subsection, we directly justify this point via the TRG flow of modular matrices on a critical point.…”
Section: Trg Flow Of Modular Matrices For a Kagome Spin Liquid Tnsmentioning
confidence: 99%
“…To understand what happens, we recall works in the tensor network literature where classical partition functions of statistical models admit a tensor network description, see for example [59,60]. These tensor network representations of partition functions, which are equivalent to Euclidean path-integrals of the quantum model in one higher dimension, can also be coarse grained, which are linear maps of the constituent tensors.…”
Section: Jhep01(2018)139mentioning
confidence: 99%
“…Generically, this problem is #P complete, and therefore, no efficient algorithm is believed to exist [9]. However, many efficient algorithms have been developed to obtain approximate solutions to this problem [10][11][12][13][14][15]. In this work, we have used both an exact, albeit inefficient, contraction algorithm and an efficient, approximate contraction algorithm for finite-sized PEPS with open boundary conditions [10].…”
mentioning
confidence: 99%